A high level estimation of the net economic benefits to small-scale livestock producers arising from animal health product distribution initiatives - Bessell, Paul R.; Salmon, Gareth; Schnier, Christian; Tjasink, Katharine; Al-Riyami, Lamyaa; Peters, Andrew (Frontiers in Veterinary Science, 2023)
A fundamental challenge for charities that facilitate distribution of animal health products to small-scale livestock producers (SSPs) in low and middle income countries (LMICs) is identifying the products and market mechanisms that provide the greatest positive impact for SSPs and estimating their associated impact. This paper describes a pragmatic approach to modelling the impact of market-led product distribution initiatives based on estimating the net economic benefit of administration of animal health products. The model estimates the economic impact of diseases at the individual animal level for poultry, small ruminants, and cattle. The economic impact of mortality and growth inhibition associated with disease are then estimated in conjunction with the losses averted or recovered by preventing or treating the disease. Economic benefit is estimated in 2014-2017 values and also adjusted to 2023 values. The flexible model structure allows for addition of new geographies, new products, and increased granularity of modelled production systems. Applied to the Global Alliance for Livestock Veterinary Medicines (GALVmed) product distribution initiatives conducted in Sub Saharan Africa (SSA) and South Asia (SA) between 2014 and 2017. The model estimates an adjusted total net economic benefit of 139.9 million USD from sales of vaccines and poultry anthelminthics in these initiatives. Within SSA, the greatest net economic benefit was realized from East Coast fever and Newcastle disease vaccines, while in SA, peste des petits ruminants and Newcastle disease vaccines had the greatest net economic benefits. This translated to an adjusted $28.89 of net economic benefit on average per SSP customer, many of whom were small poultry producers. While the model currently estimates impacts from mortality and growth inhibition in livestock, there is the potential to extend it to cover impacts of further initiatives, including interventions targeted at diseases that impact production of milk, eggs, and reproduction.